2014
DOI: 10.3892/ijmm.2014.2024
|View full text |Cite
|
Sign up to set email alerts
|

S100B is required for high glucose-induced pro-fibrotic gene expression and hypertrophy in mesangial cells

Abstract: The advanced glycation end‑product (AGE)‑receptor for AGE (RAGE) axis induces transforming growth factor‑β (TGF‑β) expression, cell hypertrophy and increases extracellular matrices that are indicated in the pathogenesis of diabetic nephropathy (DN). RAGE binds to numerous ligands besides AGE, including S100B. In the present study, the roles of S100B in high glucose‑induced p21WAF1, extracellular matrices, TGF‑βl and cell hypertrophy in mouse mesangial (MES13) cells were investigated. High glucose (30 mM) time‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Angiotensin-II, which was elevated in mesangial cells and glomerular endothelial cells, has been implicated in activating TGF-β1 by generation of ROS from nicotinamide adenine dinucleotide phosphate oxidases (Lee, 2011;Morales et al, 2012) or by activating protein kinase C-and p38 MAPK-dependent pathways (Weigert et al, 2002). Hyperglycemia, mechanical stretch, and advanced glycation end products were found to upregulate TGF-β1 in DKD (Gruden et al, 2000;Chuang et al, 2015). TSP-1, a prototypic matricellular ECM protein, was heavily deposited in glomeruli of patients with DKD (Hohenstein et al, 2008).…”
Section: Tgf-β1 Promotes Renal Fibrosis In Dkdmentioning
confidence: 99%
“…Angiotensin-II, which was elevated in mesangial cells and glomerular endothelial cells, has been implicated in activating TGF-β1 by generation of ROS from nicotinamide adenine dinucleotide phosphate oxidases (Lee, 2011;Morales et al, 2012) or by activating protein kinase C-and p38 MAPK-dependent pathways (Weigert et al, 2002). Hyperglycemia, mechanical stretch, and advanced glycation end products were found to upregulate TGF-β1 in DKD (Gruden et al, 2000;Chuang et al, 2015). TSP-1, a prototypic matricellular ECM protein, was heavily deposited in glomeruli of patients with DKD (Hohenstein et al, 2008).…”
Section: Tgf-β1 Promotes Renal Fibrosis In Dkdmentioning
confidence: 99%
“…Furthermore, hyperglycemia, ROS, proinflammatory cytokines, and advanced glycation end products were found to upregulate TGF-β1 expression in DKD [55,56]. TGF-β1 regulated fibrosis in DKD through F I G U R E 9 Avidin-biotin peroxidase for α-SMA X400: (a) control group, (b) diabetic group, and (c) treated group.…”
Section: Discussionmentioning
confidence: 99%
“…NOX4/NADPH oxidase expression is increased in pulmonary fibroblasts from patients with IPF (49), and NOX4 regulates TGF-β1-induced fibroblast differentiation by modulating activation of SMAD2/3 (49). Recently, Tsubouchi et al demonstrated that azithromycin (AZM) increases NOX4 degradation in the proteasome and exhibits an antifibrotic effect in bleomycin-injured mice (50). Interestingly, AZM increased STUB1 protein levels and proteasome activity, and AZM-mediated NOX4 degradation was dependent on STUB1 (50), indicating an antifibrotic effect of STUB1.…”
Section: Tgf-β-targeting Ubiquitin E3 Ligases In Lung Fibrosismentioning
confidence: 99%